Environmental Coordination: Reneging And Transaction Costs - Erik, Jan (Advances in Social Sciences Research Journal, 2015)
In the well-known Stern Review from 2006, global warming and climate change was described as the largest externality in the known history of mankind. When externalities take on a planetary scale, then costs will show up in various countries sooner or later, like now China, the Pacific Islands and Western US as well as India for instance. The core of the difficulty of counter-acting the process of poisening the atmosphere through the emission of greenhouse gases is the set of problems that governments encounter when they attempt collective action through coordination. These difficulties are well anaysed in game theory, but the lessons have no been drawn upon in the many international meetings aimig to tackle climate change. The tone is now optimistic ahead of the next major reunion in Paris end of this year, but it is not likely that the government of the countries of planet Earth will overcome the dismal logic of collective action, viz. reneging and tranaction costs.